2023
DOI: 10.1155/2023/1057457
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Geoelectrical and Geological Investigation of a Quaternary Paleo-Depositional Environment in the Haripur Basin, Northern Pakistan: Implications for Groundwater System

Abstract: The deposition in Haripur basin not only provides a contemporary insight into old fluvial depositional sequences of the Himalayan foreland but also sheds light on the important continental depositions in a monsoon controlled foreland system. The present study emphasizes the evaluation of the paleo-depositional architecture for sustainable groundwater availability by utilizing a total of four field-based geological observations, eleven boreholes, and fifty-nine vertical electrical sounding (VES) datasets. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…The analysis of FR for the relationship between groundwater borehole and geology percent shows that geology factor subclass Quaternary sediment has the highest FR value of 16.38 among all factor's subclasses, showing a stronger correlation with groundwater potentiality [71]. This finding corroborates the result of [83], who reported that Quaternary sediment plays a vital role in groundwater storage by providing maximum groundwater-yielding capacity for sustainable groundwater supply. This subclass constitutes about 15% of the boreholes in the study area.…”
Section: Delineation Of Potential Groundwater Potential Zones Using F...supporting
confidence: 81%
“…The analysis of FR for the relationship between groundwater borehole and geology percent shows that geology factor subclass Quaternary sediment has the highest FR value of 16.38 among all factor's subclasses, showing a stronger correlation with groundwater potentiality [71]. This finding corroborates the result of [83], who reported that Quaternary sediment plays a vital role in groundwater storage by providing maximum groundwater-yielding capacity for sustainable groundwater supply. This subclass constitutes about 15% of the boreholes in the study area.…”
Section: Delineation Of Potential Groundwater Potential Zones Using F...supporting
confidence: 81%